A nonlinear dynamic inversion-based neurocontroller for unmanned combat aerial vehicles during aerial refuelling - Pedro, Jimoh Olarewaju; Panday, Aarti; Dala, Laurent (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents the development of modelling and control strategies for a six-degree-of-freedom, unmanned combat aerial vehicle with the inclusion of the centre of gravity position travel during the straight-leg part of an in-flight refuelling manoeuvre. The centre of gravity position travel is found to have a parabolic variation with an increasing mass of aircraft.
Keywords: trim and stability analysis; neurocontroller; UCAV; aerial refuelling; nonlinear dynamic inversion